Long-Term Dynamic Monitoring of Medieval Masonry Towers - Azzara, Riccardo Mario; Girardi, Maria; Iafolla, Valerio; Padovani, Cristina; Pellegrini, Daniele (Frontiers in Built Environment, 2020)
The aim of the paper is to present and discuss the results of an ambient vibration monitoring campaign conducted in the old town of Lucca, over the period 2015-2018. Despite the low level of the ambient vibrations in the historic centre, using high-sensitivity instrumentation allowed the authors to measure and study the dynamic behavior of two medieval masonry towers: the San Frediano belfry and the Clock Tower. The main results of the dynamic identification of the towers are summarized, together with the variation over time of their dynamic properties. Some insights on the towers’ response to the anthropic activities in the historic centre are also presented. Finally, a finite element simulation is performed with the aim of assessing the influence of temperature variations on the towers’ natural frequencies; good agreement is found between numerical and experimental results. The paper provides the scientific and technical community with a detailed report on a singular experiment in the field of architectural heritage.